Living Islam: Tradisi Menyambangi Rumah Ulama Dalam Idulfitri - Rahmat Fauzi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
Abstract: this article examines the phenomenon of Living Islam in Eid al-Fitr with special reference to the people of Koto Padang Village, Sungaipenuh. It explains how the diversity of Islamic practices in local communities is influenced by differences in responses to the function of the scriptures and the local context surrounding them. It looks at how the reception of the local Islamic community towards the holy book and the pattern of interaction between religion and local culture in the tradition of visiting ulama’ houses. The function of the scriptures in history is not singular. Sources of Islamic teachings, apart from being interpreted in order to obtain the message and meaning in them (informative function), are also often understood to be actualized in concrete action (perfomative function). The comprehension process is also influenced by the local context and the situation of the reader. Based on religious and sociological studies, this paper finds that the tradition of visiting the ulamas house is one of the forms of the performing function of the scripture in the local community. The inteaction of religious understanding regarding Eid al-Fitr and respect for ulama with local culture has resulted in the practice of visiting ulamas’ houses during Eid al-Fitr. Nevertheless, this practice shows that the role of religion in influencing culture is more dominant. The values found in this tradition are this practice is a means of maintaining religious and cultural identity, respecting the ulama and moral education for the younger generation, praying as a form of good endeavor, enlivening Eid al-Fitr and fostering social cohesion